CUSTOMER INFORMATION SYSTEM DESIGN IN METRO LAUNDRY - Wendy Priawan JS; Susi Wagiyanti, SKom, MM Susi Wagiyanti, SKom, MM (Jurnal Sistem Informasi, 1999)
Customer information systems at Metro Laundry is still done manually, the data isprocessed in such a complexity of customer data, transaction data Cleaning up thedata so that it often causes the slowness of information generated, especiallyregarding the report to the CEO of the company if requested. For that it was time verynecessary and urgent to use computers as tools in data-processing data moreefficiently and accurately.The purpose of this system design is easier than getting the performance data. Thegoal of this system is:1. Providing services to the customer information needs.2. Overcoming the deficiencies that were found on systems running.3. Provide more accurate reports to the CEO.